Structural Features of Heparin and Its Interactions With Cellular Prion Protein Measured by Surface Plasmon Resonance - Kim, So Young; Zhang, Fuming; Harris, David A.; Linhardt, Robert J. (Frontiers in Molecular Biosciences, 2020)
Self-propagating form of the prion protein (PrPSc) causes many neurodegenerative diseases, such as Creutzfeldt-Jakob disease (CJD) and Gerstmann-Straussler-Scheinker syndrome (GSS). Heparin is a highly sulfated linear glycosaminoglycan (GAG) and is composed of alternating D-glucosamine and L-iduronic acid or D-glucuronic acid sugar residues. The interactions of heparin with various proteins in a domain-specific or charged-dependent manner provide key roles on many physiological and pathological processes. While GAG-PrP interactions had been previously reported, the specific glycan structures that facilitate interactions with different regions of PrP and their binding kinetics have not been systematically investigated. In this study, we performed direct binding surface plasmon resonance (SPR) assay to characterize the kinetics of heparin binding to four recombinant murine PrP constructs including full length (M23-230), a deletion mutant lacking the four histidine-containing octapeptide repeats (M23-230 ∆59-90), the isolated N-terminal domain (M23-109), and the isolated C-terminal domain (M90-230). Additionally, we found the specific structural determinants required for GAG binding to the four PrP constructs with chemically defined derivatives of heparin and other GAGs by an SPR competition assay. Our findings may be instrumental in developing designer GAGs for specific targets within the PrP to fine-tune biological and pathophysiological activities of PrP.